Understory functional groups and fire history but not experimental warming drive tree seedling performance in unmanaged boreal forests - Jessen, Maria-Theresa; Krab, Eveline J.; Lett, Signe; Nilsson, Marie-Charlotte; Teuber, Laurenz; Wardle, David A.; Dorrepaal, Ellen (Frontiers in Forests and Global Change, 2023)
Introduction: Survival and growth of tree seedlings are key processes of regeneration in forest ecosystems. However, little is known about how climate warming modulates seedling performance either directly or in interaction with understory vegetation and post-fire successional stages.Methods: We measured survival (over 3 years) and growth of seedlings of three tree species (Betula pubescens, Pinus sylvestris, and Picea abies) in a full-factorial field experiment with passive warming and removal of two plant functional groups (feather moss and/or ericaceous shrubs) along a post-fire chronosequence in an unmanaged boreal forest.Results: Warming had no effect on seedling survival over time or on relative biomass growth. Meanwhile, moss removal greatly increased seedling survival overall, while shrub removal canceled this effect for B. pubescens seedlings. In addition, B. pubescens and P. sylvestris survival benefitted most from moss removal in old forests (>260 years since last fire disturbance). In contrast to survival, seedling growth was promoted by shrub removal for two out of three species, i.e., P. sylvestris and P. abies, meaning that seedling survival and growth are governed by different understory functional groups affecting seedling performance through different mechanism and modes of action.Discussion: Our findings highlight that understory vegetation and to a lesser extent post-fire successional stage are important drivers of seedling performance while the direct effect of climate warming is not. This suggests that tree regeneration in future forests may be more responsive to changes in understory vegetation or fire regime, e.g., indirectly caused by warming, than to direct or interactive effects of rising temperatures.